Influence of alkali metal and alkaline earth metal oxides on physical and optical properties of TeO2–WO3–GdF3-R2O-ZO: Eu3+ glasses (R = Li, Na, K, Z = Mg, Ca, Ba). Issue 19 (1st October 2022) - Li, Ce; Zhang, Xu; Onah, V.C.; Yang, Weiling; Leng, Zhuang; Jiang, Xiliang; Zhang, Fangming; Li, Shasha; Zhang, Yong; Han, Yu; Liu, Huisheng; Li, Chun; et al.
Abstract: In analyzing the effect of alkali metal and alkaline earth metal oxide on the properties of tellurite glass, a series of tellurite glass samples doped with alkali metals and alkaline earth metals were prepared based on the TeO2 -WO3 -GdF3 glass system by melt quenching method. Through tests and comprehensive analysis, the results show that after the F − ions successfully enter the glass network, the substitution of TeO2 by alkali and alkaline earth metals could reduce the molar volume, which means the glass becomes more compacted. The influence on the glass network is mainly shown in [TeO3 ] and [TeO4 ] units. Alkali metals and alkaline earth metals could increase the asymmetry of the TWG: Eu 3+ glass network, shorten the critical distance, and increase luminescence intensity by 8.6 times and improve color purity to 94%. In addition, alkali metals could prolong the fluorescence lifetime, while alkaline earth metals could shorten it. Te 4+